2002
DOI: 10.1038/sj.bdj.4801478
|View full text |Cite
|
Sign up to set email alerts
|

Food and drink consumption, sociodemographic factors and dental caries in 4–5-year-old children in Amman, Jordan

Abstract: The types of foods and drinks consumed as snacks by young Jordanian children were similar to those of Western countries. In the absence of more widespread oral health promotion measures and in the presence of high prevalence and severity of caries,the oral health of Jordanian children is a matter of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 17 publications
(10 reference statements)
6
26
1
2
Order By: Relevance
“…5,6,7,8 The study also showed a strong relationship between increasing age and increase prevalence of dental caries which indicating the importance of taking preventive measures to control dental caries at the very early stage This result was quite similar with earlier findings in Bangaldesh 9 which reported an increase in caries prevalence with increasing age. The study also revealed that assisted brushing by parents at this age group could be an important factor in lowering caries incidence as young children often fail to clean their teeth in an ideal manner.…”
Section: Discussionsupporting
confidence: 82%
“…5,6,7,8 The study also showed a strong relationship between increasing age and increase prevalence of dental caries which indicating the importance of taking preventive measures to control dental caries at the very early stage This result was quite similar with earlier findings in Bangaldesh 9 which reported an increase in caries prevalence with increasing age. The study also revealed that assisted brushing by parents at this age group could be an important factor in lowering caries incidence as young children often fail to clean their teeth in an ideal manner.…”
Section: Discussionsupporting
confidence: 82%
“…3,12 It has been shown that frequent soft-drink consumption contributes to dental erosion. 13,14 A study in Kampala, Uganda showed that 24-37% of older children (10-14 years) consumed soft-drinks daily.…”
Section: Introductionmentioning
confidence: 99%
“…It is a staggering public health and economic burden to a country, particularly to developing and underdeveloped countries (Rugg-Gunn, 1993;Harel-Raviv et al, 1996). Sugars are the most important dietary etiological cause of dental caries (Sheiham, 1991;Rugg-Gunn, 1993;Harel-Raviv et al, 1996;Jamel et al, 1997;Majewski, 2001;Sheiham, 2001;Moynihan, 2002;Sayegh et al, 2002;Sanders, 2004).…”
Section: Introductionmentioning
confidence: 99%